KEUNGGULAN KOMPARATIF DAN DAMPAK KEBIJAKAN PEMERINTAH PADA PENGEMBANGAN PRODUKSI JAGUNG DI BENGKULU - IKIN ISADIKIN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2002)
The objective of this study was to analyze comparative advantage and the impact ofgovernment policy on corn production in Bengkulu. Primary and secondary data werecollected by interviewing corn farmer, traders, and marketing institutional on October 1996.The data were analyzed by using Policy Analysis Matrix (PAM). The result show thatBengkulu corn production have relatively high comparative advantage as reflected by DRCRvalue of 0.5814. The impact of goverment policy gaves disinsentif to develop corn farmers, asto reflected by the value of NPCI=1.1704, NPCO=0.859, and EPC=0.833. To increase theefficiency, the government need to deregulate input (fertilizer) subsidy so that no input pricedifferences between food crop sector and estate crop sector.